Patterned remittances enhance women's health-related autonomy - Sharon H. Green; Charlotte Wang; Swethaa S. Ballakrishnen; Hannah Brueckner; Peter Bearman (Elsevier, 2019)
The consequences for women "left behind" by virtue of temporary male migration are mixed. On the one hand, concomitant changes in fertility, participation in the labor force, and social norms are often associated with increased independence for women. On the other hand, women left behind can be vulnerable to increased dependency on members of their husbands' family or face limited access to social institutions. These shifts in women's capacity for decision making can have important implications for their health and well-being. Focusing on the state of Kerala in southern India, we examine the conditions under which the remittances that migrants send home have an impact on the health of women left behind. Specifically, we assess the extent to which the timing of remittance sending can support women's autonomy and improve their ability to make autonomous healthcare decisions. We use evidence from migrant households in Kerala, a region deeply engrained in the world labor migration system for more than five decades. Analysis is conducted with data from the 2016 wave of the Kerala Migration Survey (KMS), a representative household survey, and paired with in-depth qualitative interviews with women in Kerala whose husbands and other family members have migrated to the Gulf. We show that the positive effect of remittances on women's autonomy manifests primarily through the timing of remittance receipt, not the amount of money remitted. Regular remittances are associated with higher levels of autonomy than remittances received at irregular intervals, net of amount remitted. This finding challenges the usual emphasis on remittance volume as the driving factor of social and behavioral change in sending communities. Analytical efforts should be refocused on the social-interactional component of remittance sending and how these interactions can impact women's health and autonomy.